2020
DOI: 10.1016/j.vaa.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intramuscular vatinoxan (MK-467), co-administered with medetomidine and butorphanol, on cardiopulmonary and anaesthetic effects of intravenous ketamine in dogs

Abstract: Objective To investigate the impact of intramuscular (IM) co-administration of the peripheral a 2 -adrenoceptor agonist vatinoxan (MK-467) with medetomidine and butorphanol prior to intravenous (IV) ketamine on the cardiopulmonary and anaesthetic effects in dogs, followed by atipamezole reversal.Study design Randomized, masked crossover study.Animals A total of eight purpose-bred Beagle dogs aged 3 years.Methods Each dog was instrumented and administered two treatments 2 weeks apart: medetomidine (20 mg kg e1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The respiration rate in both the groups was depressed could be due to depression of respiratory centre located in medulla oblongata by anaesthetic agents [6,16,27,29]. Similar observation has also been reported by [24,27,29,30] where they found significant declined in respiration rate. However, [6] in their study reported that respiration rate decreased non-significantly.…”
Section: Clinico-physiological Parameterssupporting
confidence: 85%
See 1 more Smart Citation
“…The respiration rate in both the groups was depressed could be due to depression of respiratory centre located in medulla oblongata by anaesthetic agents [6,16,27,29]. Similar observation has also been reported by [24,27,29,30] where they found significant declined in respiration rate. However, [6] in their study reported that respiration rate decreased non-significantly.…”
Section: Clinico-physiological Parameterssupporting
confidence: 85%
“…-physiological parameters includes rectal temperature, respiration rate, heart rate and SpO 2 were recorded at15,30, 45 …”
mentioning
confidence: 99%